Overcoming the antinomy of determinism and freedom in P. Bourdieu`s concept of the habitus - Kusherets, Tamara (Actual Problems of Mind, 2017)
People actualize the objectified social world through the habitus, which manifests historical experience. Any historical act appears in two states: history in its objective state, accumulated in speeches, books, customs, and history in its incorporated status, which becomes a habitus.